Serum insulin-like growth factor-binding protein 2 levels as an indicator for disease severity in enterohemorrhagic Escherichia coli induced hemolytic uremic syndrome - Tasaki, Yuko (Ren Fail, 2021)
BACKGROUND: Insulin-like growth factor-binding protein (IGFBP) 2 plays an important role in the regulation of cell adhesion, migration, growth, and apoptosis. This study aimed to investigate the clinical significance of serum IGFBP2 as a biomarker for disease activity and severity in hemolytic uremic syndrome (HUS) induced by enterohemorrhagic Escherichia coli (EHEC). METHODS: IGFBP2 production by human renal glomerular endothelial cells (RGECs) after exposure to Shiga toxin 2 (Stx-2) was investigated in vitro. Serum IGFBP2 levels in blood samples obtained from 22 patients with HUS and 10 healthy controls (HCs) were quantified using an enzyme-linked immunosorbent assay. The results were compared to the clinical features of HUS and serum tau and cytokine levels. RESULTS: Stx-2 induced the production of IGFBP2 in RGECs in a dose-dependent manner. Serum IGFBP2 levels were significantly higher in patients with HUS than in HCs and correlated with disease severity. Additionally, serum IGFBP2 levels were significantly higher in patients with encephalopathy than in those without encephalopathy. A serum IGFBP2 level above 3585 pg/mL was associated with a high risk of encephalopathy. Furthermore, serum IGFBP2 levels significantly correlated with serum levels of tau and inflammatory cytokines associated with the development of HUS. CONCLUSIONS: Correlation of serum IGFBP2 level with disease activity in patients with HUS suggests that IGFBP2 may be considered as a possible indicator for disease activity and severity in HUS. Larger studies and additional experiments using various cells in central nervous system should elucidate the true value of IGFBP2 as a clinical diagnostic marker. ABBREVIATIONS: IGFBP: insulin-like growth factor-binding protein; HUS: hemolytic uremic syndrome; EHEC: enterohemorrhagic Escherichia coli; RGECs: renal glomerular endothelial cells; STx-2: Shiga toxin 2; HCs: healthy controls; LPS: lipopolysaccharide; ROC: receiver operating characteristic; sTNFR: soluble tumor necrosis factor receptor.